PENINGKATAN HASIL BELAJAR PADAMATA KULIAH KIMIA DASAR I DENGAN METODE PENDEKATAN MODIFICATION OF RECIPROCAL TEACHING (MODERAT) - Hayati, Sri Nur (Universitas Negeri Semarang, 2010)
This research was motivated by low students' achievement on Basic ChemistryI course. Students could not study autonomously and the learning process have notactivated the students. This research was conducted with class action research designwith two cycles that consist of planning, acting, observing, and reflecting. Theobtained data were analyzed by descriptive-qualitative approach. The respondentswere students of Chemistry Programme on first semester who were active on BasicChemistry I course. The intended success indicator was that at least 85% of studentspassed. The minumum passing grade was higher than 70. Based on the result anddiscussion it can be concluded that the use ofÃ‚Â Modification of Reciprocal TeachingÃ‚Â (MODERAT) approach method was able to enhance the achievement on BasicChemistry I course of students of Chemistry Department of first semester of academicyear 2008/2009.Kata kunci : hasil belajar, kimia dasar I,Ã‚Â modification of reciprocal teachingÃ‚Â (MODERAT)